Analysis of Powtoon-Based Learning Media Development in Indonesian Language Subjects - Enny Rahayu; Mutia Febriyana; Halimah Tussadiah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Student Centered Learning-based learning model which was conducted online in the midst of the Covid 19 pandemic in Indonesian language learning at SMP Muhammdiyah 01 Medan, namely in class VII junior high school students. This study uses a 4D development model (define, design, develop, and disseminate). The subjects of this study were students of SMP Muhammadiyah 01 Medan class VII-A using a small class scale totaling 25 students. Obtaining data through documentation techniques, questionnaires, observation and tests. The data analysis technique used is descriptive quantitative data analysis. The feasibility of learning media refers to the results of media assessments by the developed learning media experts. The results of this study indicate that the powtoon learning media using a student centered learning-based learning model has met the appropriate and valid criteria for use in Indonesian online learning in the midst of the Covid 19 pandemic where in this case learning activities, teacher and student interactions get a percentage of student learning completeness. The test given was 85%. Based on the results of the analysis of student learning outcomes tests, it can be concluded that student learning outcomes tests developed using Powtoon media with a student centered learning based learning model obtained complete criteria.